APPLICATION OF DATA ENVELOPMENT ANALYSIS (DEA) ON THE TECHNICAL EFFICIENCY OF ORGANIC SWAMP CABBAGE FARMING AT MUTIARA FARM, PAGELARAN VILLAGE, PAGELARAN SUB-DISTRICT, MALANG REGENCY, EAST JAVA - Sari Perwita Rahmanti; Rini Dwiastuti; Nuhfil Hanani (Socio-Economics/Agribusiness Department, 2020)
The use of inputs in producing output is an important thing to be considered in the production process. Efficiency is a measure that shows how well resources are used in the production process. This study aims to analyze: 1) technical efficiency of the amount of polybags, seeds, organic fertilizer, and working hours used in organic swamp cabbage farming at Mutiara Farm, Pagelaran Village; 2) scale efficiency level of each farmer; 3) adjustment of inputs used; 4) peers; and 5) factors that affect technical efficiency. The method used to analyze technical efficiency, scale efficiency, input usage settings, and peers is Data Envelopment Analysis (DEA). Tobit Regression is used to analyze the factors that influence efficiency level. The results showed that the use of production factors was not yet full-efficient. Average efficiency is 94%. Five farmers have scale efficiency and operate in constant return to scale. Twenty-seven farmers have scale inefficiency, which consists of 17 farmers operating in increasing returns to scale and 10 farmers operating in decreasing returns to scale. The average reduction in polybag inputs is 64, seeds are 2,743 seeds, fertilizer is 187 kg, and working hours are 16 hours. Full efficient farmers with the highest number of peers are the 27th farmer, namely as many as 19 peers. Age and farming experience affect the value of technical efficiency. Age variable has a more dominant influence than farming experience.